CEO overconfidence and the influence on firm innovation: s study about well-established multinationals during 2008-2016 - Vermaut, David (2020)
Previous research has mainly investigated the effect of CEO overconfidence on financial outcomes. However, only little research has been conducted about the influence of CEO overconfidence on firm innovation. Moreover, no studies have examined when CEO background characteristics such as tenure and power distance, influence the latter relationship. Consequently, the purpose of this master’s thesis is to analyze the impact of CEO overconfidence on firm innovation, and to explore whether tenure and power distance influence this relationship. Using shareholder letters to measure overconfidence, the results indicate that over the 2008-2016 period, CEO overconfidence positively influences firm innovation for well established-multinationals active in non-innovative industries. Nonetheless, for well-established multinationals in innovative industries, there exists no relationship between CEO overconfidence and innovation. Furthermore, in line with the theoretical research, the findings demonstrate a negative moderating impact of tenure in both innovative and non-innovative industries. Unlike CEO tenure, the influence of CEO power distance could not be investigated due to correlational issues with both CEO overconfidence and CEO tenure. By highlighting the importance of CEO overconfidence in explaining a valuable organizational outcome such as firm innovation and by unveiling the moderating impact of CEO tenure, the thesis contributes to the existing upper-echelons and tone-at-the-top literature.